Fipronil in sub-lethal doses leads to immuno-toxicological effects in broiler birds - Shafia Tehseen Gul; Muhammad Zergham Tahir; Latif Ahmad; Aisha Khatoon; Muhammad Kashif Saleemi; Farid Shokry Ataya; Riaz Hussain; Bakhtawar Maqbool; Dalia Fouad; Ahrar Khan (PLoS ONE, 2025)
Pesticides, including fipronil, are used mainly in agriculture; however, in veterinary and animal husbandry, their potential use is to control the pests responsible for vector-borne diseases. Their residues in agriculture products and direct use on farms are responsible for potentially harming livestock and poultry. So, this study was designed to evaluate the toxico-pathological effects of fipronil on the immune system of poultry birds. One hundred a-day-old chicks were purchased from a local hatchery, and standard housing conditions were provided from brooding till the end of the trail. The temperature at brooding was kept at 33°C; later on, it was maintained at 26–28°C, and the humidity was at 60–70%. Clean water and a basal diet were provided ad libitum. After three days of acclimatization, birds were divided into five experimental groups (A to E), each containing 20 birds. Group A was kept as a control group. Fipronil was administered orally through crop tubing @ 1.5, 2.5, 3.5, and 4.5 mg/kg to groups B-E, respectively. Birds were euthanized humanely on the 15th, 30th, and 45th days of the experiment. Immunological parameters were evaluated, i.e., antibody titers against NDV and SRBCs, phagocytic activity to clear carbon particles, avian incompetence to avian tuberculin, and histopathological alterations in the lymphoid organs. The SAS® University Edition software was used for data analysis. The results indicated decreased antibody titers against NDV in the treatment groups compared to the control. Similarly, antibody response to SRBCs, phagocytic activity in clearing the carbon particles, and sensitivity to avian tuberculin in the treatment groups were also decreased. Results also revealed that the bursa of Fabricius thymus and spleen were also affected due to the toxic effect of fipronil, even at sub-lethal doses.